Transformation of Frontier National Parks into Tourism Sites. The North Andean Patagonia Experience (1934-1955) - Vejsbjerg, Laila (2014)
Fil: Vejsbjerg, Laila. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Patagonia Norte; Argentina